Eksistensi Talempong Kayu di Nagari Durian Gadang Kecamatan Sijunjung Kabupaten Sijunjung - Sri Aprillia Nura; Asril Asril; Yurnalis Yurnalis (SENDRATASIK UNP, 2023)
This research examines the existence of Talempong Kayu in Nagari Durian Gadang, Sijunjung District, Sijunjung Regency. Talempong Kayu is one of the traditional music in Nagari Durian Gadang. Initially, Talempong Kayu was performed using one instrument, namely a set of wooden talempongs consisting of five blades. The function of Talempong Kayu is to entertain yourself when you are tired from work or during your spare time. Along with the times, Talempong Kayu has developed and does not only use one instrument, but has added accompaniment instruments such as two drums, a gong and a bottle. The function of Talempong Kayu has also developed, such as entertainment events, the appointment of traditional titles, events commemorating the anniversary of Sijunjung Regency, entertainment at weddings, as well as events to welcome guests of government agencies. The purpose of this study was to describe the existence and form of presentation and function of Talempong Kayu in Nagari Durian Gadang, Sijunjung District, Sijunjung Regency. This study uses qualitative research methods with data collection techniques by observation, documentation, and field interviews to obtain research results according to the context that is descriptive. The results of this study explain that the existence of Talempong Kayu traditional music in Nagari Durian Gadang has experienced developments both in terms of tools and in terms of its use in society.